Contagion Effect Krisis Argentina dan Turki ke Negara-Negara Asia, Benarkah Terjadi? - Setiawan, Adi; Kartiasih, Fitri (Jurnal Ekonomi dan Pembangunan Indonesia, 2021)
This study aims to examine the contagion effect of the Argentinian and Turkish crises to Asian countries using the DCC-MGARCH model. The data used is the daily closing price index of the stock index obtained from Thomson Reuters DataStream covering form the period of January 2, 2014 to May 17, 2019. The results showed that the contagion effect of the Argentinian crisis occurred in Malaysia, Korea, Thailand and the Philippines, while Indonesia, Singapore, India and China are only interdependence. The pure contagion test results also show that the contagion effect of the Turkish crisis occurred in Indonesia, Malaysia, the Philippines, Thailand, India, and China, while Singapore and Korea only interdependence with the Turkish market.